Continuing education and teaching practice: interlocutions with teachers of a law course in the pandemic period (Revista Contexto & Educação, 2024)
The expansion of higher education, especially in the last three decades, has placed as a backdrop the concern with teacher training. In this context, the research is structured from the investigative problem: how do professors of the Bachelor's Degree in Law at a Community University of Santa Catarina perceive the importance of continuing education for their teaching activity? The objective is to analyze the perception of teachers regarding continuing education and their teaching practices, in view of the pandemic scenario. This is a qualitative, exploratory, descriptive and interpretive research, with an analytical approach and a hypothetical-deductive method. Twelve teachers were interviewed using the focus group technique. The collected data were organized in the Atlas TI software and submitted to Bardin's Content Analysis (1977), considering the following categories: course and identification, online classes and pandemic, competence movements, active methodologies, teacher training and expectations . The results show that the participants have pedagogical weaknesses that can be “improved” with continuing education programs and that the Covid-19 pandemic has destabilized the teaching-learning processes, making it difficult to evaluate and develop pedagogical practices that motivate students to participate in classes.
Keywords: College education; Continuing Training; Law course; Pandemic